Performance evaluation and analysis by simulation for sliding mode control with speed regulation of permanent magnet synchronous motor drives in electric vehicles - Senani, F.; Rahab, A.; Benalla, H. (Національний технічний університет "Харківський політехнічний інститут", 2025)
This study introduces a sliding mode control (SMC) that utilizes multivariable system command estimation (MSCE-SMC) to create an innovative speed control system for the permanent magnet synchronous motor (PMSM). The motor operates through a 3-phase voltage source inverter when used in an electric vehicle (EV) model, with the goal of achieving fast speed regulation and high performance. Problem. The primary challenge is to achieve fast and accurate speed regulation for PMSMs while maintaining high performance, despite varying system parameters and external disturbances. The goal is to design a robust and adaptive speed control system for PMSMs using the SMC approach, which ensures precise speed tracking and high-performance regulation. Scientific novelty. The integration of MSCE-SMC approach, offering an innovative solution for speed control in PMSMs used in EVs. Methodology. SMC approach for the PMSM divides the system into 2 subsystems: electrical and speed. A d-q coordinate frame is used to model the PMSM, and its control strategy is outlined. A detailed model of the PMSM with SMC is presented after an in-depth review of the theoretical concepts and principles of sliding mode control. Results. To validate the proposed approach, MATLAB/Simulink is conducted, demonstrating the effectiveness and robustness of the method in PMSM speed regulation. The results confirm that the proposed method provides straightforward and precise control, accurate speed tracking, and high-performance regulation. It also shows adaptability to parameter variations and external disturbances. Practical value. The practical value of the proposed method is significant, as it provides a reliable and efficient control system for PMSMs. It offers precise speed control, robust performance under variable conditions, and high adaptability to external disturbances, making it suitable for real-world EV applications.

У дослідженні розглядається керування ковзним режимом (SMC), що використовує багатопараметричну оцінку системних команд (MSCE-SMC) для створення інноваційної системи керування швидкістю синхронного двигуна з постійними магнітами (PMSM). Двигун працює через трифазний інвертор напруги при використанні в моделі електромобіля (EV) з метою досягнення швидкого регулювання швидкості та високої продуктивності. Проблема. Основне завдання полягає в досягненні швидкого і точного регулювання швидкості для PMSM при збереженні високої продуктивності, незважаючи на параметри системи, що змінюються, і зовнішні збурення. Метою є розробка надійної та адаптивної системи керування швидкістю для PMSM з використанням SMC підходу, що забезпечує точне відстеження швидкості та високопродуктивне регулювання. Наукова новизна. Інтеграція підходу MSCE-SMC пропонує інноваційне рішення для управління швидкістю PMSM, що використовуються в EV. Методологія. SMC підхід для PMSM поділяє систему на 2 підсистеми: електричну та швидкісну. Для моделювання PMSM використовується d-q система координат і описується стратегія його управління. Наведено докладну модель PMSM з SMC після поглибленого аналізу теоретичних концепцій та принципів управління в ковзному режимі. Результати. Для перевірки пропонованого підходу проведено аналіз у середовищі MATLAB/Simulink, що показав ефективність та надійність методу регулювання швидкості PMSM. Результати підтверджують, що запропонований метод забезпечує просте і точне керування, коректне відстеження швидкості та високопродуктивне регулювання. Він також демонструє адаптивність до змін параметрів та зовнішніх збурень. Практична цінність запропонованого методу значна, оскільки він забезпечує надійну та ефективну систему управління PMSM. Він забезпечує точне управління швидкістю, надійну роботу в змінних умовах, і високу адаптивність до зовнішніх збурень, що робить його придатним для застосування в реальних EV.
Keywords: permanent magnet synchronous motor; sliding mode control; electric vehicle; speed regulation; синхронний двигун з постійними магнітами; керування ковзним режимом; електромобіль; регулювання швидкості